Simulação computacional de escoamentos turbulentos gás-sólido - Ferreira, Stella Rodrigues (2016)
The presence of solid particles in industrial turbulent flows in complex geometries witnessed in engineering. The analysis of the velocity of the particle, and of its trajectory in the flow of gas-solid a complex task and of paramount importance. In the present work the Euler-Lagrange approach was used, where the dispersed phase treated in the Lagrangean reference and the equations that govern the continuous phase are solved in the Eulerian reference. One of the advantages of the Immersed Boundary Method that immersed geometry is also represented in the Lagrangian reference. It is important to emphasize that one of the advantages of the Immersed Boundary Methodology is the ability to solve the flow using Cartesian meshes in the presence of complex geometries. For the present work, it was possible to predict complex multiphase flows, combining promising methodologies such as SLE and Immersed Border Methodology.